PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP HARGA SAHAM STUDI PADA PERUSAHAAN SUBSEKTOR BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2021. - Priangga Ersa Yolansyah, - (2023)
This objective of this research aims to determine the effect of Return on Equity, Earnings per Share, Total Assets Turnover, and Sales Growth on Stock Prices in coal subsector companies for the 2018-2021 period. This research design is a quantitative research with a causal approach. The population in this study are all companies in the coal subsector which are listed on the Indonesia Stock Exchange with a total of 32 companies. The sampling technique used in this study was purposive sampling. Testing the hypothesis using multiple linear regression analysis using a statistical tool in the form of SPSS (Statistical Program for Social Science) software version 25. The results showed that partially Return on Equity, Total Assets Turnover, and Sales Growth have an effect and positive on stock prices. While partially Earnings per Share has no effect and negative on stock prices. Simultaneously the research yields that Return on Equity, Earnings per Share, Total Assets Turnover, and Sales Growth which have an effect and positive on stock prices.